Trots’ O. Linguistic representation of Old-Germanic magic arts: comparative aspect - Trots’ O. (Philological Treatises, 2020)
The article deals with lexical units to denote Old Norse magic arts with their translation into Ukrainian, supplying further interpretation and clarification of lexical meaning. Key Old Icelandic lexemes – seiðr, spá and galðrar – reflect the ethnic preculiarities of Germanic tribes of the XI–XIII c.